Central Mucoepidermoid Carcinoma: A Case Report - Polat, Şenol; Serin, Gediz; Aksoy, Elif; Üneri, Cüneyd (Fırat University, 2011)
Mucoepidermoid carcinomas originating from the mandible are rare and called as central mucoepidermoid carcinomas. These tumors make up approximately 2-3 % of all salivary gland tumors, have a predilection for women and the majority occurs in 4th and 5th decades of life. The origin of the tumor was speculated to be presence of ectopic salivary gland tissue. Clinical presentations are slow growing swelling, pain, tooth mobility and trismus. Surgery is the manstay of treatment for this tumor and en block resection of the tumor should be done. Postoperative radiotherapy is recommended for better prognosis. A case of this uncommon malignant tumor of a 74 year-old female patient is presented.

Mandibuladan kaynaklanan mukoepidermoid karsinomlar nadir görülür ve santral mukoepidermoid karsinom olarak adlandırılır. Bu tümörler tükrük bezi tümörlerinin yaklaşık % 2-3'ünü oluşturur, daha sık kadınlarda ve çoğunluğu 40 ile 50 yaşları arasında görülür. Tümör kökeninin ektopik tükrük bezi dokusunun varlığına bağlı olduğu öne sürülmüştür. Klinik olarak yavaş büyüyen şişlik, ağrı, dişlerde oynama ve trismus ile prezente olurlar. Bu tümörün temel tedavisi cerrahi eksizyondur ve en-block rezeksiyon gereklidir. Daha iyi prognoz için operasyon sonrası radyoterapi önerilmektedir. Sık görülmeyen bu tümörü olan 74 yaşında kadın hasta olgu olarak sunuldu.
Santral Mukoepidermoid Karsinom: Olgu Sunum